Geoheritage and geoparks - Brilha, J. B. (2018)
Geoparks are territories with a sustainable development strategy based on the conservation of geoheritage and its use in educational and geotourism activities, together with other natural and cultural resources of the territory. Geoparks gained the international distinction label ‘UNESCO Global Geoparks’ in 2015. The geoheritage of each geopark is the core of its strategy and therefore needs to be properly identified, assessed, conserved and managed. This chapter gives some guidelines about these procedures and presents some examples, particularly addressed to geopark managers and to those involved with geopark projects.